Phase 1, open-label, dose-escalation study on the safety, pharmacokinetics, and preliminary efficacy of intravenous Coxsackievirus A21 (V937), with or without pembrolizumab, in patients with advanced solid tumors. Issue 1 (20th January 2023) - Rudin, Charles M; Pandha, Hardev S; Zibelman, Matthew; Akerley, Wallace L; Harrington, Kevin J; Day, Daphne; Hill, Andrew G; O'Day, Steven J; Clay, Timothy D; Wright, Gavin M; Jennens, Ross R; Gerber, David E; et al.
Abstract : Background: Oncolytic virus V937 showed activity and safety with intratumoral administration. This phase 1 study evaluated intravenous V937±pembrolizumab in patients with advanced solid tumors. Methods: Patients had advanced non-small cell lung cancer (NSCLC), urothelial cancer, metastatic castration-resistant prostate cancer, or melanoma in part A (V937 monotherapy), and metastatic NSCLC or urothelial cancer in part B (V937+pembrolizumab). Prior immunotherapy was permitted >28 days before study treatment. Patients received intravenous V937 on days 1, 3, and 5 (also on day 8 in part B) of the first 21-day cycle and on day 1 of subsequent cycles for eight cycles. Three ascending dose-escalation cohorts were studied. Dose-escalation proceeded if no dose-limiting toxicities (DLTs) occurred in cycle 1 of the previous cohort. In part B, patients also received pembrolizumab 200 mg every 3 weeks from day 8 for 2 years; dose-expansion occurred at the highest-dose cohort. Serial biopsies were performed. Results: No DLTs occurred in parts A (n=18) or B (n=85). Grade 3–5 treatment-related adverse events (AEs) were not observed in part A and were experienced by 10 (12%) patients in part B. The most frequent treatment-related AEs (any grade) in part B were fatigue (36%), pruritus (18%), myalgia (14%), diarrhea (13%), pyrexia (13%), influenza-like illness (12%), and nausea (12%). At the highest tested dose, median intratumoral V937 concentrations were 117, 631 copies/mL on day 8, cycle 1 in part A (n=6) and below the detection limit for most patients (86% (19/22)) on day 15, cycle 1 in part B. Objective response rates were 6% (part A), 9% in the NSCLC dose-expansion cohort (n=43), and 20% in the urothelial cancer dose-expansion cohort (n=35). Conclusions: Intravenous V937+pembrolizumab had a manageable safety profile. Although V937 was detected in tumor tissue, in NSCLC and urothelial cancer, efficacy was not greater than that observed in previous studies with pembrolizumab monotherapy. Trial registration number: NCT02043665 .